Sistem Kontrol Suhu dan Laju Pemanasan Alat Pirolisis - Muhammad Amiruddin; Bambang Sutopo; Rochmadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
In the process of pyrolysis, heating rate and temperature is an important parameter to be controlled, because it affects the results of the process. Temperature of the heating process in the heating chamber dimensions 35cm × 20cm × 20cm, monitored with a thermocouple type K that have a measurement range of -200°C to 1300°C. Setting the heating element uses AC voltage control TRIAC phase control method. Control system using fuzzy logic control with input variable E (error), CE (change of error), the delay time of TRIAC trigger and temperature process to produce a variable output of delay time change of TRIAC trigger involving fuzzy rules. The results of this study have produced a system of control ranges from 0° to 700°C, and is able to provide maximum heating rate of 9.9°C/min over a temperature range of 100°C to 200°C and heating rate of a minimum of 4, 4°C/min over a temperature range of 600°C to 700°C. In descriptive statistics, temperature control has a maximum temperature range in 8.9°C at 700°C setpoint and the maximum standard deviation of 2.2 at 500°C setpoint.